Structure and dynamics of herbaceous layer vegetation of artificial Caragana intermedia shrublands in desert steppe - Zhao Wei; Yang Mingxiu; Chen Lin; Wang Lei; Song Naiping; Yang Xinguo (浙江大学学报. 农业与生命科学版)
Caragana intermedia is a leguminous shrub plant, which is planted in desert steppe area on a large scale, which can also be used as forage grass, with very important ecological and economic value. However, a series of shrub and grass resource competition problem emerged with the aging of C. intermedia shrublands. The growth of zonal perennial vegetation often subjected to great constraints, and self-degradation of C. intermedia shrublands was also developed to different degrees. The reasonable collocation relations of shrub and grass were one of the key elements to maintain ecology and production services of C. intermedia shrublands in desert steppe. The objective of this study is to understand composition characteristics of herbaceous plant species and its dynamic change rules around the C. intermedia shrublands, and to reveal the structure of shrub and grass and the evolution trend of C. intermedia shrubland system.Taking natural grassland as a control, spatiotemporal substitution methods were used, and a research sequence constituted of different ages of C. intermedia shrubland plots was erected to carry out tracking, monitoring and analysis of vegetation seasonal dynamics at interior and exterior of the shrubs.The results showed that: 1) The number of natural grassland (CK) and herbaceous plant species of C. intermedia shrublands were 25 species, belonging to 8 families and 23 genera. The highest species number was the 16 a C. intermedia shrublands (16 species), and the number of species gradually decreased with aging of C. intermedia shrublands. Pennisetum centrasiaticum, Cleistogenes squarrosa and other perennial grasses began to appear, but the dominant species still was short-lived annual plants. Species diversity indexes showed a decreasing trend after a steady increase with aging of C. intermedia shrublands. 2) The seasonal dynamics, coverage degree, aboveground biomass and species number of herbaceous layer vegetation were mainly affected by the change of precipitation and temperature, but the existence of C. intermedia shrubs delayed the growth recovery rate of herbaceous layer vegetation after spring drought, and the highest relative volatility index was 25 a C. intermedia shrublands. 3) The coverage degree of herbaceous layer vegetation at the interior and exterior of the C. intermedia shrubs and the seasonal dynamics of aboveground biomass at the interior of the C. intermedia shrubs were significantly changed by the ages of C. intermedia shrubland, and a significant interaction between ages of C. intermedia shrublands and seasonal factors was observed.In conclusion, the structure and dynamics of herbaceous layer vegetation of C. intermedia shrublands in desert steppe is regulated by the ages of C. intermedia shrublands, season and spatial heterogeneity and so on. With the decay of C. intermedia shrublands, the community gradually grows towards zonal vegetation succession, but under the circumstance of short-lived annual plants as dominant species, maintenance of system stability and succession direction still has many uncertainties.